The CLV3 Homolog in Setaria viridis Selectively Controls Inflorescence Meristem Size - Zhu, Chuanmei; Liu, Lei; Crowell, Olivia; Zhao, Hui; Brutnell, Thomas P.; Jackson, David; Kellogg, Elizabeth A. (Frontiers in Plant Science, 2021)
The CLAVATA pathway controls meristem size during inflorescence development in both eudicots and grasses, and is initiated by peptide ligands encoded by CLV3/ESR-related (CLE) genes. While CLV3 controls all shoot meristems in Arabidopsis, evidence from cereal grasses indicates that different meristem types are regulated by different CLE peptides. The rice peptide FON2 primarily controls the size of the floral meristem, whereas the orthologous peptides CLE7 and CLE14 in maize have their most dramatic effects on inflorescence and branch meristems, hinting at diversification among CLE responses in the grasses. Setaria viridis is more closely related to maize than to rice, so can be used to test whether the maize CLE network can be generalized to all members of subfamily Panicoideae. We used CRISPR-Cas9 in S. viridis to knock out the SvFON2 gene, the closest homolog to CLV3 and FON2. Svfon2 mutants developed larger inflorescence meristems, as in maize, but had normal floral meristems, unlike Osfon2, suggesting a panicoid-specific CLE network. Vegetative traits such as plant height, tiller number and leaf number were not significantly different between mutant and wild type plants, but time to heading was shorter in the mutants. In situ hybridization showed strong expression of Svfon2 in the inflorescence and branch meristems, consistent with the mutant phenotype. Using bioinformatic analysis, we predicted the co-expression network of SvFON2 and its signaling components, which included genes known to control inflorescence architecture in maize as well as genes of unknown function. The similarity between SvFON2 function in Setaria and maize suggests that its developmental specialization in inflorescence meristem control may be shared among panicoid grasses.